Implementation of Independent Learning: Chemobio-Enterpreneurship in Junior High School - Sri Adelila Sari; Ameilia Zuliyanti Siregar; Faidul Rasyid Hutabarat (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS (JPBN), 2023)
In order to achieve learning objectives that can assist students in discovering and understanding chemical and biological concepts related to everyday life, an approach is needed that is able to make chemistry and biology material a very interesting and important subject to study and understand. The Chemo-Bio Entrepreneurship (CBEP) approach incorporates entrepreneurial values into learning according to the demands of independent learning. This is in response to the needs of the Industrial Revolution 4.0 era. The purpose of this research was to help motivate teachers and students to have an entrepreneurial spirit. In addition, learning chemistry and biology will be more fun and provide opportunities for students to optimize their potential to produce products. Thus, the economy of the school community can be developed, as a source of financial input for schools. The research samples were students and teachers of Junior High School 3 Tanjung Morawa 3, Deli Serdang which were taken using purposive sampling. The methods used were observation, interviews, Focus Group Discussion (FGD) and training in making compost and natural hand sanitizers. Data were analyzed using qualitative and quantitative descriptive statistics. The results showed that the understanding and skills of students and teachers before and after being given training in making compost and natural hand sanitizers were found to be increased. It was suggested to science teachers and school members to continue to practice good practices and be able to pass them on to teachers of other subjects. Thus, the productivity of teachers and students as entrepreneurs is well maintained